Reproducibility of the Endometriosis Fertility Index: a prospective inter‐/intra‐rater agreement study. (31st July 2019) - Tomassetti, C; Bafort, C; Meuleman, C; Welkenhuysen, M; Fieuws, S; D'Hooghe, T
Abstract : Objective: To evaluate the reproducibility of the Endometriosis Fertility Index (EFI). Design: Single‐cohort prospective observational study. Setting: University hospital. Population: Women undergoing laparoscopic resection of any rASRM‐stage endometriosis. Methods: Details of pre‐ and peroperative findings were collected into a coded research file. EFI scoring was performed en‐bloc by three different raters (expert‐1 [C.T.], expert‐2 [C.M.], junior [C.B.]). Required sample size: 71. Definitions used for agreement: clinical (scores within same range: 0–4, 5–6, 7–10) and numerical (difference ≤1 EFI point). Main outcome measures: Primary outcome : rate of clinical agreement between two experts. Secondary outcomes : expert numerical agreement, clinical and numerical agreement between expert‐1 and junior, and within expert‐1 (intra‐observer), agreement of rASRM score and ‐stage. Results: A near 'inter‐expert' clinical agreement rate (1.000, 95% CI 0.956‐1.000; P  = 0.0149) was observed. The numerical agreement between two experts was also high (0.988, 95% CI 0.934–1.000); similarly, high agreement rates were observed for both 'junior–expert' comparisons (clinical 0 .963, 95% CI 0.897–0.992; numerical 0.988, 95% CI 0.934–1.000) and 'intra‐expert' comparisons (clinical 0.988, 95% CI 0.934–1.000; numerical 1.000, 95% CI 0.956–1.000). Reasons for disagreements were different scoring of the least‐function score and disagreements in rASRM scores. The reproducibility of the rASRM score was clearly inferior to that of the EFI for all comparisons. Conclusion: The EFI can be reproduced reliably by different raters, further supporting its use in daily clinical practice as the principal clinical tool for postoperative fertility counselling/management of women with endometriosis. Tweetable abstract: A study confirming the high reproducibility of the EFI substantiates its use in daily clinical practice. Tweetable abstract: A study confirming the high reproducibility of the EFI substantiates its use in daily clinical practice.